(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
Post-war poetry, written in the aftermath of the World Wars, offers a powerful reflection on the lingering psychological, emotional, and societal effects of armed conflict. Following the devastation of both World War I and World War II, poets grappled with the legacy of war, exploring themes of trauma, loss, disillusionment, and the collapse of traditional values. While the immediate response to war poetry often centered on the horrors of battle, post-war poetry focused on the long-term consequences of violence—both on the individuals who fought and on the societies left to rebuild. Poets such as W.B. Yeats, T.S. Eliot, Randall Jarrell, and Denise Levertov delved into the moral and psychological scars left by war, giving voice to the profound sense of alienation, grief, and hopelessness that war’s aftermath engendered. This poetry also raised questions about the resilience of human society in the face of such destruction and the possibility of renewal. Furthermore, post-war poetry often engaged with a broader critique of modernity, addressing the ways in which war revealed the fragility of civilization and exposed the darker sides of human nature. The examination of this body of work highlights not only the personal trauma and suffering caused by war but also the collective struggle for meaning, reconciliation, and the pursuit of peace in the face of overwhelming loss and devastation. Ultimately, post-war poetry stands as both a memorial and a critique, offering a poignant reminder of the enduring human costs of conflict and the urgent need to reflect on its lasting impact.